FZD6 expression is negatively regulated by miR-199a-5p in human colorectal cancer - Kim, Bong-Kyu (BMB Rep, 2015)
Colorectal cancer (CRC), the third most common cancer worldwide, also has the highest rate of cancer-related morbidity and mortality. WNT signaling is initiated by binding of WNT to various receptors, including frizzleds (FZDs), and plays a critical role in CRC and other tumor development by regulating proliferation, differentiation, migration, apoptosis, and polarity. Among the members of the FZD family, FZD6 is broadly expressed in various tissues, and its overexpression has been reported in several cancers, suggesting an important role in cancer development. In this study, we investigated the expression of FZD6 in patients with CRC and found it to be increased in tumors, as compared to paired adjacent non-tumor tissues. Additionally, we found that FZD6 expression was negatively regulated by miR199a5p in CRC cells. These results suggest that overexpression of FZD6, mediated by reduced expression of miR-199a-5p, may play an important role in the development of CRC. [BMB Reports 2015; 48(6): 360-366]